2005
DOI: 10.1093/eurheartj/ehi291
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized heart failure in elderly patients with stable chronic obstructive pulmonary disease

Abstract: Unrecognized heart failure is very common in elderly patients with stable chronic obstructive pulmonary disease. Closer co-operation among general practitioners, pulmonologists, and cardiologists is necessary to improve detection and adequate treatment of heart failure in this large patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
277
5
20

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 389 publications
(318 citation statements)
references
References 38 publications
16
277
5
20
Order By: Relevance
“…Furthermore, many countries have shown that diagnostic tests are not consistently conducted in all patients with suspected HF (38). Diagnosis of HF is challenging, and cases can be misclassified under other diseases because symptoms can be nonspecific to HF, particularly in the elderly (39).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many countries have shown that diagnostic tests are not consistently conducted in all patients with suspected HF (38). Diagnosis of HF is challenging, and cases can be misclassified under other diseases because symptoms can be nonspecific to HF, particularly in the elderly (39).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of chronic heart failure (CHF) in patients with chronic obstructive pulmonary disease (COPD) is known to range from 20% to 32% [1][2][3][4][5][6][7]. This high prevalence of CHF in patients with COPD is not surprising, because COPD and CHF share smoking as a common risk factor, and, moreover, it is likely that low-grade systemic inflammation accelerates progression of coronary atherosclerosis, which ultimately results in ischemic cardiomyopathy [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the twelve-week placebocontrolled study in moderate-to-severe COPD demonstrated no cardiovascular effects of FFIS treatment using standard ECG and Holter monitoring [Nelson et al 2007], and other controlled studies of low-dose LABA treatment for COPD have reached the same conclusion [Campbell et al 2007;Ogale et al 2006;Ferguson et al 2003]. Therefore, it is difficult to determine if the observed deaths were related to treatment or the underlying cardiovascular comorbidities often associated with COPD [Sin et al 2006;Rutten et al 2005;Shih et al 1988]. …”
Section: Discussionmentioning
confidence: 99%